The Birth of the Surabaya Chinese School during the Dutch Colonial Period - Eko Satriya Hermawan; Rojil Nugroho Bayu Aji (The Indonesian Journal of Social Studies, 2020)
The discussion about the existence of the Chinese ethnic in the midst of the development of the city of Surabaya is the initial part of writing this research. This article tries to reveal the Education Dynamics of Chinese Children in Surabaya during the Dutch Colonial Period. Chinese-Javanese relations are very close, even the existence of ethnic Chinese as one of the social entities in the city community is also a subject of discussion, to find out the dynamics of education and social changes in the city of Surabaya. The history of the city cannot be separated from the socio-political dynamics of society, which must begin with education. The development of the city affects the character and behavior of a person in society. To achieve this goal, historical methods are used, which include: heuristics, criticism, interpretation, and historiography. The result achieved is that "the Chinese community of Surabaya through education gives birth to new ideas that have an influence on the decolonization process" which will be explained in this article.